Physiology of peritoneal dialysis; pathophysiology in long-term patients - Krediet, Raymond T. (Frontiers in Physiology, 2024)
The microvascular wall of peritoneal tissues is the main barrier in solute and water transport in the initial phase of peritoneal dialysis (PD). Small solute transport is mainly by diffusion through inter-endothelial pores, as is hydrostatic fluid transport with dissolved solutes. Water is also transported through the intra-endothelial water channel aquaporin-1(AQP-1) by a glucose-induced crystalloid osmotic gradient (free water transport). In the current review the physiology of peritoneal transport will be discussed both during the first years of PD and after long-term treatment with emphasis on the peritoneal interstitial tissue and its role in free water transport. Attention will be paid to the role of glucose-induced pseudohypoxia causing both increased expression of fibrogenetic factors and of the glucose transporter GLUT-1. The former leads to peritoneal fibrosis, the latter to a reduced crystalloid osmotic gradient, explaining the decrease in free water transport as a cause of ultrafiltration failure. These phenomena strongly suggest that the extremely high dialysate glucose concentrations are the driving force of both morphologic and functional peritoneal alterations that may develop during long-term PD.